Encyclopedia of Superstitions. - Radford, Mona A. (Philosophical Library/Open Road, 2018)
This classic and thoroughly delightful reference explores the origins of superstitions. You'll discover the origins behind charms, spells, fairy lore and legend, folk remedies and customs of birth, marriage, and death. This collection will be a staple in your library for years and generations to come.